A noção de intersubjetividade nas Meditações Cartesianas de Edmund Husserl - Sanchez, Devair Gonçalves (2014)
This research aims to present a reading of the notion of intersubjectivity based on the Cartesian Meditations work of Edmund Husserl. For this, will be demonstrated, how, from of solipsism to the formation of a Intermonadologic universal community, Husserl offers a proposal for theoretical reasoning about knowledge of the alter ego, based on the status of phenomenology as transcendental idealism. At first moment, will be done an approach of the major concepts of phenomenology contained in the work, and that arise in the first meditations until the theoretical core of the question: the Fifth Meditation. In the intermediate section will be prioritized the description of the donation modes of the alter ego to ego through the constitutive dynamic. Finally, will be explained the formation of communities of higher grade as a result of the unity of monadic egos and response at the problem of intersubjectivity.